Complex internal rearrangement processes triggered by electron transfer to acetic acid - Limão-Vieira, P. (2020)
IF-FCT IF/00380/2014. PLV the research grants PTDC/FIS ATO/1832/2012. SFRH/BD/52538/2014. Doctoral Trainning Programme (RaBBiT, PD-F, PD/00193/2012). Spanish Ministerio de Economía y Competitividad (Project No. FIS 2009-10245). Some of this work forms part of the EU/ESF COST Action CM1401, Our Astro-Chemical History.